Preventing Radicalism: Islamic Moderation and Revitalization in the Border - Ibrahim Ibrahim; Zaenuddin Hudi Prasojo; S. Sulaiman (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2019)
The growing radical and extreme ideologies recently are not only a concern but also a threat to the social relations of harmony and human peace, including in the border region of Kapuas Hulu, Kalimantan. It is important to spread moderate Islamic teaching to counter this extreme ideology to the people in the border region of Kapuas Hulu. This research examines the roles of religious leaders and religious institutions in disseminating moderate Islam in the border region of Kapuas Hulu to counter the growing influence of radical-extremism. This research employs a qualitative method and the data from field research is presented descriptively. This research shows that religious leaders and religious institutions exist in almost every sub-district in the border region. They teach messages of Islamic moderation that include four principles namely the concept of tawasuth-moderate, tawazun-equality, tasamuh-tolerant, and i`tidal. This principle must be strengthened as a foundation in behaving, acting, speaking, socializing, and living in the Indonesian nation and state. It is on these values and principles that religious leaders and religious institutions reinforce their role in preaching, guiding and fostering people in the border region.